Do neuroendocrine carcinomas and mixed neuroendocrine–non-neuroendocrine neoplasm of the gastrointestinal tract have the same prognosis? A SEER database analysis of 12, 878 cases. (July 2020) - Shi, Huiying; Qi, Cuihua; Meng, Lingjun; Yao, Hailing; Jiang, Chen; Fan, Mengke; Pang, Suya; Zhang, Qin; Lin, Rong
Background: Neuroendocrine carcinomas (NECs) and mixed neuroendocrine–non-neuroendocrine neoplasm (MiNEN) in the gastrointestinal (GI) tract are both rare and malignant; however, it is unclear whether their prognosis is the same. Methods: In this cross-sectional study, a total of 12, 878 patients with NEC or MiNEN in the GI tract were reviewed retrospectively by searching the Surveillance, Epidemiology, and End Results ( SEER ) program database. Next, we compared the characteristics and survival between patients with NEC or MiNEN and further analyzed the prognostic factors for the patients. Results: The data showed that patients with MiNEN had a worse prognosis as compared with patients with pure NEC in the small intestine (SI) and appendix, whereas there was no significant survival difference between NEC and MiNEN in the other parts of the GI system. On the whole, age ⩾55 years ( p < 0.0001), male ( p = 0.002), being diagnosed at TNM Stage II–IV ( p < 0.0001) or not receiving surgical treatment ( p < 0.0001) were the independent negative prognostic factors for NEC patients, whereas age ⩾55 years ( p = 0.003), being diagnosed at TNM Stage III–IV ( p < 0.001) or not receiving surgical treatment ( p < 0.001) were identified as the independent negative prognostic factors for the MiNEN patients. Furthermore, when NECs or MiNENs were classified based on the primary tumor site, the results showed that the prognostic factors for NEC and MiNEN varied between the tumor sites. Conclusion: The prognostic differences between NECs and MiNENs in the GI tract are heterogeneous and site-related. Patients with appendiceal or SI MiNEN have a poorer prognosis than patients with pure appendiceal or SI NEC. Therefore, we should pay more attention to patients with MiNEN in the SI and appendix and monitor them more closely.